Geografija v vrtcih in na razredni stopnji osnovne šole v Sloveniji - Umek, Maja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
The paper elucidates to what extent and with what contents geography is included in syllabuses from the preschool period to the fifth grade, its quantity relation to other sub - jects, and syllabus changes to be sought in future reforms. We analysed curriculums that incorporate geographical contents, with the use of qualitative and semi-quantitative analysis. Encoding categories comprised landscape elements, regions, orientation and cartography.
Keywords: curriculum; geografija; geography; kurikulum; osnovne šole; otroški vrtci; Slovenia; Slovenija; učni načrti; učni programi